Peran Guru Pendidikan Agama Islam Dalam Mengatasi Kenakalan Siswa - Takrim, Donna; Zuhdiyah, Zuhdiyah; Sofyan, Sofyan; Muhammad Kashif Majeed; Syarnubi, Syarnubi; Irja Putra Pratama (PAI RAFAH, 2025)
Student delinquency is one of the challenges faced in the school environment, especially at the junior high school level. This research aims to analyze the role of Islamic Religious Education (PAI) teachers in dealing with student delinquency. The research method used is descriptive qualitative with field research type with data collection techniques in the form of interviews, observation and documentation.The research results show that PAI teachers have a strategic role as educators, advisors, role models, mentors and motivators in shaping student character. PAI teachers apply various strategies, such as providing an understanding of religious values, holding group discussions, and taking a personal approach to students who have problems. Apart from that, collaboration between PAI teachers and Guidance and Counseling (BK) teachers is an important factor in creating effective solutions. In addition, the study highlights that the integration of religious education in school culture contributes significantly to the prevention and reduction of student delinquency. Therefore, strengthening the role of PAI teachers is essential in fostering disciplined, responsible, and ethical behavior among students.